2012
DOI: 10.1016/j.jtcvs.2011.10.046
|View full text |Cite
|
Sign up to set email alerts
|

A novel detection method of non–small cell lung cancer using multiplexed bead-based serum biomarker profiling

Abstract: We confirmed that a new diagnostic method using 5 serum biomarkers profiling constructed by multivariate classification algorithms could distinguish NSCLC from healthy controls with high accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 22 publications
(22 reference statements)
2
25
0
Order By: Relevance
“…Among the validated proteins, we have confirmed the previously reported over-expression of CRP and HPT acutephase proteins in lung cancer patients, 2,24 as well as CO4A complement factor, 25 indicating a chronic active inflammation state and immune response. Recent proteomic studies showed alterations of different acute-phase proteins in distinct tumor types, which enhanced their usefulness as specific cancer biomarkers.…”
Section: Discussionsupporting
confidence: 82%
“…Among the validated proteins, we have confirmed the previously reported over-expression of CRP and HPT acutephase proteins in lung cancer patients, 2,24 as well as CO4A complement factor, 25 indicating a chronic active inflammation state and immune response. Recent proteomic studies showed alterations of different acute-phase proteins in distinct tumor types, which enhanced their usefulness as specific cancer biomarkers.…”
Section: Discussionsupporting
confidence: 82%
“…Comparing BSI to the bead-based assay is difficult in this case, but the BSI LOQ (not the LOD at 2σ) exhibits >1.5-fold improvement and is performed as a free-solution and label-free method. 49,50 Electrochemiluminescence assays have demonstrated detection limits comparable to ours reported here, 25,49,50 yet these assays are expensive and require substantial chemical complexity in both the assay discovery and analytical validation phase.…”
Section: Results and Discussionsupporting
confidence: 63%
“…For example Lee et al recently reported the quantification of Cyfra 21-1 using Luminex at levels as low as 0.01 ng/mL. 49 They present data for healthy patients ranging from 0.01 to 0.73 ng/mL and cancer patients having 0.66 to 2.4 ng/mL, yet the manufacturer reports a minimum detection concentration at 2 times the standard deviation of 0.059 ng/mL. Here we use a more conservative measure of performance, the LOQ, which is based on 3 times the standard deviation of the assay run over 5 days.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Such biomarkers are available and will be studied in the future for lung cancer detection (Choi et al, 2012; Takenaka et al, 2011; Tretiakova et al, 2011; Pesta et al, 2011; Lee et al, 2012; Tong et al, 2012; Ohira et al, 2003). Physical methods to further increase PC microcavity sensitivity are being investigated including optimization of PC microcavity length, the slow light effect in coupled PC waveguides and PC microcavity resonance mode quality factors (Chakravarty et al, 2012; Lai et al, 2012).…”
Section: Resultsmentioning
confidence: 99%